Education on the Benefits of Drinking Milk as a Source of Protein and Calcium for Elementary School Students - Dian Ayu Juwita; Nadila Oktavia; Rahmah Rahmah (Warta Pengabdian Andalas, 2024)
Optimal nutrition plays a crucial role in supporting the growth and development processes of children. One abundant and easily accessible source of nutrition is milk. The protein and calcium content in milk support bone formation, brain development, and various bodily functions. This community service activity aims to provide education to elementary school students about the benefits of milk as a nutritional source and to enhance milk consumption habits. Education is conducted through face-to-face interactions using lecture and discussion methods. The material is presented through PowerPoint presentations, videos, and the distribution of leaflets to the participants. To assess the success of the educational activities, pretests and posttests are conducted on the participants. The results of the educational activities show an increase in the average posttest scores compared to the pretest scores regarding the benefits of drinking milk. This indicates that the educational activities have successfully improved the participants' understanding of the importance of including milk in a healthy diet.